The impact of corporate social responsibility on innovation in small and medium‐sized enterprises: The mediating role of debt terms and human capital - Santos‐Jaén, José Manuel; Madrid‐Guijarro, Antonia; García‐Pérez‐de‐Lema, Domingo (Corporate Social Responsibility & Environmental Management, 2021)
The aim of this paper is to study the influence of corporate social responsibility (CSR) over small and medium‐sized enterprise (SME) innovation and the effect of two mediating variables, debt terms and human capital. Based on a sample of 2825 Spanish SMEs and applying a structural equations modeling, the results demonstrate that the effect of CSR on innovation is mediated by debt terms and by good human resource practices. Part of the positive effect of CSR on innovation occurs through these two variables, which, alone, positively and significantly affect innovation in SMEs. Consequently, the positive effect of CSR practices on debt terms through a decrease in asymmetric information goes further, also having repercussions on innovation. Additionally, the suitable development of human resource practices based on strategies oriented toward CSR allow companies to carry out greater and more efficient innovative activities. This paper contributes to the CSR literature considering the human resource management and the debt access in the relationship between CSR and innovation. The findings reveal important implications for policy makers and managers. For the former, the results show that it would be interesting to carry out actions aimed at assisting SMEs, especially those with fewer resources available, to implement a suitable CSR strategy, supporting sustainable development in SMEs. And, for the latter, CSR‐oriented innovation has proven to be a valuable strategy for more efficient SMEs management because of the multiple competitive advantages it generates.
Keywords: Europe; Responsabilité sociétale des entreprises; Réservé UdeM

Social Innovation and University Intellectual Property: Insights from the UK and Mexico - McDonagh, L.; Bonadio, E.; Alba Betancourt, A. (European Intellectual Property Review, 2020)
University intellectual property policies, and the accompanying strategies for incubation of IP via licensing and spin outs, have not received much analysis from academic lawyers. Moreover, despite the success of universities in the UK at generating income from IP, not much is known about how transferable this success is when considered in the light of a rapidly growing middle-income developing economy such as Mexico’s. In this article we analyse critically some of the key tenets of IP policies at universities in the UK to identify what the key legal principles underpinning university innovation are. We further consider the potential application of these principles in Mexico, where so far only a limited number of universities have developed IP policies and strategies in line with the incubator model. We explain how universities in Mexico could implement these research findings in their own IP policies. We further note that the mere provision of an IP policy is not a panacea – on its own it is insufficient for ensuring technology transfer and it may even encourage unnecessary patenting. Further investment in infrastructure and in establishing a culture of incubation and entrepreneurship is also required.
Keywords: Amérique latine; Europe; Libre accès; Propriété intellectuelle; UK